Make Data Count: Advancing meaningful evaluation of open data - Iratxe Puebla, DataCite (My University, 2025)
In this webinar presentation, Iratxe shares key updates from Make Data Count ongoing projects, including insights from the Data Citation Corpus, a large, open collection of data citations, and the work with HELIOS Open to advance the implementation of data evaluation in institutional assessment processes. She also highlights practical ways in which the community can get involved with data evaluation today.
Despite advances in open data, crucial questions remain about how data are being used and for what purposes. The Make Data Count initiative is driving progress on this front by building tools and community practices that help better measure, understand, and recognize the use and impact of data as an important research output.
Keywords: Research Data; Open Data; Data Evaluation; Open Data Monitoring; Datasets; Open Infastructure